The proportion of oesophageal adenocarcinoma patients with prior barrett's oesophagus: results from a large population based cohort. (13th March 2011) - Bhat, S; Coleman, H G; McManus, D; Gavin, A T; Murray, L J; Johnston, B T
Abstract : Introduction: Barrett's oesophagus (BO) is a premalignant condition that predisposes to oesophageal adenocarcinoma (OAC). BO is difficult to detect due to the asymptomatic nature of the condition. Prognosis from OAC is generally poor and population screening for BO has been suggested in order to increase detection and surveillance of BO. To date there has been no population based study that determined the proportion of OAC patients who had a prior diagnosis of BO. The aim of this study was to estimate the proportion of OAC patients with a prior BO diagnosis and to compare outcomes of these patients with those having no prior diagnosis of BO. Methods: The Northern Ireland Barrett's register (NIBR) is a large population based register hosted within the Northern Ireland Cancer registry (NICR) of all patients in Northern Ireland diagnosed with BO between 1993 and 2005. Data on all patients diagnosed with OAC between 2003 and 2005 were obtained from the NICR database. This data was matched to the NIBR to identify patients with OAC that had a prior diagnosis of BO. Mortality data until the end of December 2008 was obtained through the Northern Ireland Registrar General's office. Patients undergoing surgical resection were identified through hospital episode statistics. Survival analysis was conducted comparing cancer cases with or without a prior BO diagnosis. Results: 487 patients were diagnosed with OAC in Northern Ireland between 2003 and 2005. Male: Female ratio 2.7:1. A total of 34 patients had a prior diagnosis of BO (6.9%). OAC patients with a prior BO diagnosis were younger at OAC diagnosis than those without (mean age 68.4 years vs 70.1 years); this difference however was not significant (p=0.42). OAC patients with prior BO were significantly more likely to have undergone surgical resection than those without (41.2% vs 20.8%; p=0.006). Adjusted survival analysis showed that OAC patients with prior BO had a reduced risk of death compared to those with no prior BO. Conclusion: The proportion of OAC patients with prior clinically detected BO is small. The significant difference seen in surgical resection rates between the groups suggests that patients with prior BO are detected at an earlier OAC stage than those without. Survival analysis suggesting a survival advantage for those with prior BO is likely to be influenced by both lead time and length time bias. Current strategies for the detection of BO in the population identify only a small proportion of those that eventually progress to adenocarcinoma.